Overview of Delivery Complications Using IKAlin Instruments in Bandar Lampung - Octaviana, Amrina; Roslina, Roslina; Elmeida, Ika Fitria; Nurlaila, Nurlaila; Indrasari, Nelly; Rosmadewi, Rosmadewi (Poltekkes Kemenkes Tanjung Karang, 2024)
The maternal mortality rate (MMR) in Lampung Province in 2020 has increased compared to 2019, namely from 110 cases to 115 cases. Bandar Lampung City is one of the regions in Lampung Province with the third highest MMR, 10 cases (8.69%). This research aims to determine the description of childbirth complications experienced by postpartum mothers using the IKAlin instrument (Labour Complications Instrument) in Bandar Lampung in 2023. This type of research uses a descriptive survey method with random sampling. A sample of 222 postpartum mothers with labor complications. This research method involves interviews with postpartum mothers using the IKAlin instrument. The average results of mothers' answers show that the complication of preeclampsia that is felt is high blood pressure, the bleeding complication that is most often felt during labor is experiencing heavy bleeding, and the complication of dystocia that is most often felt is undergoing a prolonged second stage. The advice given is to encourage education about early detection in the community so that people, especially pregnant women, are aware of the importance of monthly pregnancy checks at health facilities to detect birth complications as early as possible.